The reception of the law relating to Res Gestae in Malaysia - Mohamad Yunus, Mohamad Ismail (Research Centre, International Islamic University Malaysia, 2006)
The LAW of EVIDENCE is termed as the eyes of the law. It is one essential legal tools that govern the aspect of proof that will determine whether certain kind of evidence tendered before the court is relevant, admissible otherwise. This is very important in order to have a fair trial and to establish justice. This research will analyses whether the doctrine of Res Gestae (a common law legal concept) which literally means "the thing done", a transaction or essential circumstances surrounding facts which are so closely connected to the fact in issue. Legally, it means circumstances, which are spontaneous and contemporaneous, or unplanned incidents of a particular litigated act, is relevant and thus admissible fact under the Malaysian Law. In most cases appear before the court of law, there is a fact story behind each of such cases, and each fact story contains several acts, omissions and statements. When evidence is given of such acts omissions and statements, although they are not in issue, but are capable of throwing some light upon the nature of transactions, revealing its true quality and character which may constitute a relevant fact. Such acts omissions and statements are regarded, as part of the same transaction and the bottom line issue here is that whether such facts are allowed to be proved? If yes, to what extent does the admissibility apply? If no, what is the different approach taken by the Malaysian Courts compared to the Common Law principle?